Mimesis: foot washing from Luke to John - Yoder, Keith L. ca. 20./21. Jh. (Ephemerides theologicae Lovanienses, 2016)
This paper argues that the Foot Washing of John 13, as literary composition, is a creative imitation, or mimesis, of the Sinful Woman narrative of Luke 7. Maurits Sabbe first noticed this connection in 1982, but his suggestion fell from scholarly discussion before it was ever fully developed. A fresh examination of the two texts now reveals a large array of previously unsurveyed parallels. Evaluation of old and new evidence shows first, that the two narratives share multiple structural and linguistic features, demonstrating a literary rather than oral connection. Second, the density, order, and distinctiveness of the parallels prove the connection to be mimetic. Finally, directional markers within the textual evidence indicate that the flow of literary influence was from Luke to John, a result validated by new interpretive options that these findings provide for John’s text.